Indications for open hepatectomy in the era of laparoscopic liver resection: a high volume single institutional study - Sung Jun Jo; Jinsoo Rhu; Jong Man Kim; Gyu-Seong Choi; Jae-Won Joh (Korean Liver Cancer Association, 2022)
Background/Aim Since the introduction of laparoscopy for liver resection in the 1990s, the performance of laparoscopic liver resection (LLR) has been steadily increasing. However, there is currently no data on the extent to which laparoscopy is used for liver resection. Herein, we investigated the extent to which laparoscopy is performed in liver resection and sought to determine whether surgeons prefer laparoscopy or laparotomy in the posterosuperior (PS) segment. Methods For this retrospective observational study, we enrolled patients who had undergone liver resection at the Samsung Medical Center between January 2020 and December 2021. The proportion of LLR in liver resection was calculated, and the incidence and causes of open conversion were investigated. Results A total of 1,095 patients were included in this study. LLR accounted for 79% of the total liver resections. The percentage of previous hepatectomy (16.2% vs. 5.9%, P<0.001) and maximum tumor size (median 4.8 vs. 2.8, P<0.001) were higher in the open liver resection (OLR) group. Subgroup analysis revealed that tumor size (median 6.3 vs. 2.9, P<0.001) and surgical extent (P<0.001) in the OLR group were larger than those in the LLR group. The most common cause of open conversion (OC) was adhesion (57%), and all OC patients had tumors in the PS. Conclusions We investigated the recent preference of practical surgeons in liver resection, and found that surgeons preferred OLR to LLR when treating a large tumor located in the PS.